2-DOF Vertical Planner Manipulator - Melhem, Tareq; Abulehia, Anas (Palestine Polytechnic University , mechanical engineering , mechatronics, 2016)
Our graduation project is 2-DOF Vertical Planner Manipulator, simply the manipulator has do two main functions, ﬁrst one is perform any 2-D sketch in vertical plane, second one is to be able to repeat a predetermined motion (teach the required motion by moving the head, then it has to repeat that motion.
CD, 29334, no of pages 40 ,ميكاترونيكس 2/2016, in the store
Keywords: 2-DOF Vertical Planner Manipulator